Post-Traumatic Growth and Protection From Burnout in Teachers During the COVID-19 Pandemic - Sokal, Laura; Eblie Trudel, Lesley; Heaman-Warne, Carl (Alberta Journal of Educational Research, 2023)
Teachers have demonstrated a wide range of responses to the challenges of teaching within a pandemic. The current study investigated the relationship between resilience and post-traumatic growth in teachers during the COVID-19 pandemic. Based on administration of the Maslach Burnout Inventory in 2022, four teachers demonstrated high levels of resilience, indicating the potential that they had experienced post-traumatic growth. Follow-up interviews were therefore conducted to investigate whether these teachers demonstrated all seven characteristics of post-traumatic growth. Although all four resilient teachers indicated experiencing several characteristics, only two teachers demonstrated post-traumatic growth. The findings support a clear distinction between resilience and post-traumatic growth. Implications related to future research using both qualitative and quantitative methods to further illuminate the processes and conditions of post-traumatic growth are discussed. Keywords: Post-traumatic growth, teachers, pandemic, resilience, Canada Les enseignants ont fait preuve d'un large éventail de réactions face aux défis de l'enseignement dans le cadre d'une pandémie. La présente étude a examiné la relation entre la résilience et la croissance post-traumatique chez les enseignants pendant la pandémie de COVID-19. L'administration du Maslach Burnout Inventory, un questionnaire évaluant les symptômes de l’épuisement professionnel, en 2022 a révélé des niveaux élevés de résilience chez quatre enseignants, indiquant la possibilité qu'ils aient connu une croissance post-traumatique. Des entrevues de suivi ont donc été menés pour déterminer si ces enseignants présentaient les sept caractéristiques de la croissance post-traumatique. Bien que les quatre enseignants résilients aient indiqué avoir vécu plusieurs de ces éléments, seuls deux enseignants ont fait preuve d'une croissance post-traumatique. Les résultats soutiennent une distinction claire entre la résilience et la croissance post-traumatique. L’article discute des implications liées aux recherches futures utilisant des méthodes qualitatives et quantitatives pour éclairer davantage les processus et les conditions de la croissance post-traumatique. Mots clés : croissance post-traumatique, enseignants, pandémie, résilience, Canada